2003
DOI: 10.1128/mcb.23.16.5939-5946.2003
|View full text |Cite
|
Sign up to set email alerts
|

Replication Checkpoint Kinase Cds1 Regulates Recombinational Repair Protein Rad60

Abstract: Genome integrity is protected by Cds1 (Chk2), a checkpoint kinase that stabilizes arrested replication forks. How Cds1 accomplishes this task is unknown. We report that Cds1 interacts with Rad60, a protein required for recombinational repair in fission yeast. Cds1 activation triggers Rad60 phosphorylation and nuclear delocalization. A Rad60 mutant that inhibits regulation by Cds1 renders cells specifically sensitive to replication fork arrest. Genetic and biochemical studies indicate that Rad60 functions codep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
117
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 49 publications
5
117
0
Order By: Relevance
“…The Rfp1-SUMO interaction was predictable based on the identification of SIM motifs in Rfp1. Uniquely, Rad60 and its homologues share the structural feature of tandem SLDs at their C-termini ( Figure 5A; (Boddy et al, 2003;Novatchkova et al, 2005)). Therefore, we tested for interaction between Rfp1 and the Rad60 SLDs.…”
Section: Identification Of Dna Repair Protein Rad60 As a Potential Slmentioning
confidence: 99%
“…The Rfp1-SUMO interaction was predictable based on the identification of SIM motifs in Rfp1. Uniquely, Rad60 and its homologues share the structural feature of tandem SLDs at their C-termini ( Figure 5A; (Boddy et al, 2003;Novatchkova et al, 2005)). Therefore, we tested for interaction between Rfp1 and the Rad60 SLDs.…”
Section: Identification Of Dna Repair Protein Rad60 As a Potential Slmentioning
confidence: 99%
“…The Rad60 -Smc5ϩ6 physical interaction and the overlapping set of genetic interactions displayed by rad60 and nse mutants suggests that these proteins have codependent functions (Morishita et al, 2002;. Unlike the Nse proteins, however, Rad60 interacts weakly with components of the Smc5ϩ6 complex (Morishita et al, 2002;Boddy et al, 2003;McDonald et al, 2003). That is, the Nse proteins coprecipitate robustly with the Smc5ϩ6 complex components when expressed at their endogenous levels ( Figure 1, B and C; McDonald et al, 2003).…”
mentioning
confidence: 99%
“…Proteins in the eluate were precipitated and subjected to mass spectrometry analysis. We have used this system extensively for identification of protein complexes in S. pombe and have thus generated a comprehensive list of common background proteins (Boddy et al, 2001;Boddy et al, 2003;McDonald et al, 2003). Comparison of the Smc5-TAP data set with previous purifications allowed us to exclude common background such as ribosomal proteins, abundant metabolic enzymes, and actin.…”
mentioning
confidence: 99%
“…p53 promotes DNA repair or apoptosis by directly regulating the expression of genes such as p48, DR5, BAX, PUMA and NOXA [2,8]. CHK2 (cds1) in fission yeast was shown to interact with RAD60, a protein required for recombinational repair, at stalled replication forks [9]. In mammalian cells, it was shown that CHK2 promotes homologous recombination (HR) and non-homologous end-joining (NHEJ) of DNA double-strand breaks through phosphorylation of BRCA1 on serine 988 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%